Community livelihoods and forest dependency: Tourism contribution in Nyungwe National Park, Rwanda - Akayezu, Providence; Ndagijimana, Isidore; Dushimumukiza, Marie Claire; Bernhard, Katie P.; Groen, Thomas A. (Frontiers in Conservation Science, 2022)
Communities living adjacent to protected areas in Africa are characterized by high poverty rates and their well-being often depends on park resources. This often results in forest degradation and decline in wildlife populations, for example due to illegal hunting for bush meat. To counter this challenge in Rwanda, a tourism revenue sharing program was initiated in 2005, with 5% (doubled to 10% in 2017) of the park gate fees invested in community development projects. We evaluated the effectiveness of this tourism revenue sharing from 2005 to 2017, targeting communities adjacent to Nyungwe National Park located in south-western Rwanda. We used questionnaires addressed to members of community associations and local government in 24 sectors around Nyungwe National Park. Additionally, data on illegal resource use and socio-economic status of the surrounding communities were obtained to quantitatively triangulate and draw insights from communities’perceptions. Using spatial analyses and spatial regression, we mapped trends in illegal activities relative to socio-economic characteristics. Both the qualitative and quantitative results indicate that the tourism revenue sharing program has not fully succeeded in improving community well-being around Nyungwe National Park. The tourism revenue sharing can consider targeting areas that demonstrate more need and reassessing prioritization of interventions supported by the program to achieve both poverty reduction around Nyungwe National Park and improved conservation outcomes in this protected area.